Moralitas Pasar dalam Hadis-Hadis Kontradiktif: Perspektif Pendekatan Kontekstual - Agus Miswanto (Universitas Ahmad Dahlan, 2022)
This research is a qualitative descriptive research on market morality in contradictory hadiths. The market is a place of economic activity for traders in order to gain profits which often ignores moral values. The focus of this research is on the traditions about the market which contain contradictions, especially those contained in the Sahih Bukhari and Sahih Muslim books. To obtain relevant data, this study uses keywords and an online search instrument, al-maktabah al-syamila. To understand the hadith of the prophet comprehensively, this study uses a contextual approach through historical and hermeneutic methods, namely looking at the text and context, and using the unification and synchronization method (al-jam' wa al-taufiq). From this study it was found that the prophet's expression which stated that the most hated place by Allah was the market, not in the textual sense, but was an expression of the prophet regarding some market activities carried out by traders which were prohibited by the Shari'a. The moral hazard behavior of traders including usury, gharar, maisir, which causes injustice and harm to other parties must be avoided and shunned.